Impact of immunotherapy time-of-day infusion on survival and immunologic correlates in patients with metastatic renal cell carcinoma: a multicenter cohort analysis - Haydn Kissick; Viraj A Master; Mehmet A Bilen; Zachary S Buchwald; Mohammad K Khan; Caroline S Jansen; Michael C Lowe; Jimmy S Patel; Yena Woo; Amber Draper; Jennifer W Carlisle; Pasquale F Innominato; et al. (Journal for ImmunoTherapy of Cancer)
Background Recent studies have demonstrated that earlier time-of-day infusion of immune checkpoint inhibitors (ICIs) is associated with longer progression-free survival (PFS) and overall survival (OS) among patients with metastatic melanoma and non-small cell lung cancer. These data are in line with growing preclinical evidence that the adaptive immune response may be more effectively stimulated earlier in the day. We sought to determine the impact of time-of-day ICI infusions on outcomes among patients with metastatic renal cell carcinoma (mRCC).Methods The treatment records of all patients with stage IV RCC who began ICI therapy within a multicenter academic hospital system between 2015 and 2020 were reviewed. The associations between the proportion of ICI infusions administered prior to noon (denoting morning infusions) and PFS and OS were evaluated using univariate and multivariable Cox proportional hazards regression.Results In this study, 201 patients with mRCC (28% women) received ICIs and were followed over a median of 18 months (IQR 5–30). The median age at the time of ICI initiation was 63 years (IQR 56–70). 101 patients (50%) received ≥20% of their ICI infusions prior to noon (Group A) and 100 patients (50%) received <20% of infusions prior to noon (Group B). Across the two comparison groups, initial ICI agents consisted of nivolumab (58%), nivolumab plus ipilimumab (34%), and pembrolizumab (8%). On univariate analysis, patients in Group A had longer PFS and OS compared with those in Group B (PFS HR 0.67, 95% CI 0.48 to 0.94, Punivar=0.020; OS HR 0.57, 95% CI 0.34 to 0.95, Punivar=0.033). These significant findings persisted following multivariable adjustment for age, sex, performance status, International Metastatic RCC Database Consortium risk score, pretreatment lactate dehydrogenase, histology, and presence of bone, brain, and liver metastases (PFS HR 0.70, 95% CI 0.50 to 0.98, Pmultivar=0.040; OS HR 0.57, 95% CI 0.33 to 0.98, Pmultivar=0.043).Conclusions Patients with mRCC may benefit from earlier time-of-day receipt of ICIs. Our findings are consistent with established mechanisms of chrono-immunology, as well as with preceding analogous studies in melanoma and lung cancer. Additional prospective randomized trials are warranted.